SOIL MESO-FAUNA PATTERNS AND EXPERIMENTS ON LEAF LITTER MITE FUNGIVORY: PREFERENCES, EFFECTS ON FUNGAL REPRODUCTION AND DECOMPOSITION - Guevara, Roger; Villedo, Lorenzo; Nájera, Andrea (Instituto de Ecología, A.C., 2002)
We investigated patterns of community structure of soil meso-fauna in an tropical cloud forest. The leaf litter habitat and the actual soil below were found to support structurally different communities. Leaf litter appeared to be a complex, heterogeneous, habitat whereas soil was homogeneous. The abundance of mites and collembolans marked the main differences between leaf litter and soil, and given that a large number of species of these taxa are fungivorous their distribution patterns are discussed in relation to those factors that may determine fungal activity. In microcosmos experiments we found that a fungivorous oppid mite (Oppidae) affected the spore production of four species of fungi suggesting a shift in their combative abilities.